INNOVATIONS IN MUSICAL AND INSTRUMENTAL TRAINING FOR PROSPECTIVE MUSICAL ART BACHELORS - Ashykhmina , Nataliia (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article explores a probable pathway for constructing the content of musical-instrumental training for prospective musical art bachelors based on an analysis of the innovative system. The author identifies the criteria for selecting the content of musical and instrumental training and hypothesizes that innovative design of this training is based on a cultural and praxeological methodological approach aimed at developing student's musical-pedagogical culture.